Kronistka M. Klementina Kastelec (1887-1963) in njena "vojna kronika" (1914-1918) - Kogoj, Marija Jasna (Acta ecclesiastica Sloveniae, 2024)
The article presents the Ursuline M. Klementina Kastelec (1887–1963), born in Vinja vas near Novo mesto, Podgrad parish. From among her immediate family came several priests who left a visible mark in the history of the Church in Slovenia. These included her brother Matija, a priest of many years in Dol pri Ljubljani. Following a thorough deliberation after completing teacher training at the Ursuline Convent in Ljubljana, she decided to become an Ursuline herself. She started her order formation in 1910, while in 1912 she became a teacher at the Ursuline day public school. In 1914, she started teaching at both the Ursuline day and boarders’ public school. It was the year that the First World War broke out, which had an impact on the work of all the schools and the Ursuline Convent. M. Klementina Kastelec described in detail the events during the First World War within the convent walls, as a branch of a military hospital was established in the convent or its school premises to shelter wounded and sick soldiers. Today the description of the experience of war in Ljubljana or the so-called War Chronicle is kept by the Archive of the Ursuline Convent and is now introduced to the wider public in the article before us.
Keywords: chronicle; First World War; Kastelec, M. Klementina; kronika; prva svetovna vojna; Ursuline convent in Ljubljana; uršulinski samostan v Ljubljani